Analysis of selected commodity flows by water transport in the Chao Phya basin - Chaiwat Changwatchai; Jones, John Hugh; Chai Muktabhant; Arbhabhirama Anat; Asian Institute of Technology (Bangkok : Asian Institute of Technology, 1968)
Thailand is a country of rivers and canals. The waterways of the central plain region are an important means of transporting cargo. This research is an attempt to describe the patterns of movement of selected commodities produced in the central plain region of Thailand and transported to Bangkok by the inland waterway system. The gravity model was investigated to ascertain its applicability to the movements of rice and maize. For rice., calibration of the gravity model for the entire study area failed. It was concluded that travel time had no measurable effect on the rice traffic. The study area was then divided to reflect the location and condition of waterways. The movement of rice from changwads near Bangkok, and chiefly connected to it by canals, generally conformed to the concept of the gravity model. The model was calibrated for two sets of data; correlation coefficients were 0.6 and 0.9. The movement of rice to Bangkok from the northern changwads, located along the main rivers, appeared to be contrary to the concept of the gravity model. It was found that the quantity of rice transported was a direct, rather than inverse, function of the travel time. However, the model was calibrated; for one set of data the correlation coefficient was only 0.07, for the second set of data the correlation was 0.6 The quantity of rice transported from each upcountry changwad to Bangkok appeared to be related to the net production in the changwad. A parabolic curve was fitted to the data; coefficients of 0.8 and 0.7 for the two sets of data resulted from this analysis. An attempt was made to apply the gravity model to the movement of maize along the inland waterways from upcountry changwads to Bangkok. The scatter of data was so great that it was apparent that no rational analysis of the available data would be possible
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in the .Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology, 1968
Keywords: Waterways -- Thailand